ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA TENTARA NASIONAL INDONESIA DI KOMANDO DISTRIK MILITER 0618/BS KOTA BANDUNG - Yusuf, Farida Nuraeni; Irawati, R. Ira; Halimah, Mas (Jurnal Governansi, 2019)
The Indonesian National Army performance in 0618/BS Military District Command of Bandung City is influenced by many factors. The purpose of this research is to find out the most dominant factors influencing the Indonesian National Army performance in 0618/BS Military District Command of Bandung City. The method of this research is the mixed method that the researchers use two methods, namely quantitative and qualitative methods. The techniques of data collection are observation, questionnaires using Likert’s scale, interview, and literature study. In this research, the researchers analyze five factors, namely personal factor, leadership factor, team factor, system factor, and contextual factor. Based on five factors, the results of the analysis indicate that the most dominant factor is the personal factor. It means that the Indonesian National Army is an idealized work and the members of the Indonesian National Army happily conduct the work. Moreover, the second factor that dominantly influences the performance is the leadership factor. It means that the leader mostly influences the Indonesian National Army performance in 0618/BS Military District Command. Keywords: Employee Performance, Performance Factors, TNI.